Book Review: EMMANUEL PASCHOS - CHRISTOS SIMELIDIS, Introduction to Astronomy by Theodore Metochites (Stoicheiosis Astronomike 1.5-30), Singapore - Hackensack, NJ: World Scientific 2017 - TELELIS, Ioannis (Byzantina Symmeikta, 2017)
Book Review:: EMMANUEL PASCHOS - CHRISTOS SIMELIDIS, Introduction to Astronomy by Theodore Metochites (Stoicheiosis Astronomike 1.5-30), Singapore - Hackensack, NJ: World Scientific 2017